(untitled) (Journal of the College of Basic Education, 2026)
In the current study (the effect of artificial intelligence in improving indoor artificial waterfalls), the researchers studied artificial intelligence programs and their impact on improving the design of indoor waterfalls, which saves the effort and time needed to improve them. By using the scientific capabilities of the designer in directing these applications and using appropriate standards according to the scientific foundations studied from the inputs that contribute to enriching the improvement of internal waterfalls and to clarify this. The researchers conducted experiments using the artificial intelligence program Midjourney, which demonstrates the researchers’ abilities to generate designs with logical descriptions in interior design. The most important .